2017
DOI: 10.1590/1516-4446-2016-2035
|View full text |Cite
|
Sign up to set email alerts
|

TBARS and BDNF levels in newborns exposed to crack/cocaine during pregnancy: a comparative study

Abstract: Objectives: To compare levels of a marker of lipid peroxidation (thiobarbituric acid reactive substances, TBARS) and brain-derived neurotrophic factor (BDNF) in umbilical cord blood (UCB) between newborns exposed to crack/cocaine in utero (exposed newborns [EN], n=57) and nonexposed newborns (NEN, n=99), as well as in maternal peripheral blood at delivery. Methods: This was a cross-sectional study. Potential confounders, including perinatal parameters, psychopathology, and use of other substances, were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…The effects of crack on mothers and their children exposed to crack in utero are very divergent 7,8 and this manifestation may continue after birth, both through breastfeeding and passive inhalation, resulting in long-term effects of the drug in the child's organism. Research have observed that newborns exposed to crack in utero express neuroprotectors and increase the levels of neurotrophic factors, while their mothers do not 7,8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of crack on mothers and their children exposed to crack in utero are very divergent 7,8 and this manifestation may continue after birth, both through breastfeeding and passive inhalation, resulting in long-term effects of the drug in the child's organism. Research have observed that newborns exposed to crack in utero express neuroprotectors and increase the levels of neurotrophic factors, while their mothers do not 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…Drug use during pregnancy can bring consequences to babies. Recent studies show babies with smaller than normal head circumference, lower birth weight, premature birth, congenital malformations, and future problems such as neurobehavioral problems in childhood and adolescence [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mardini et al (2017) measured the BDNF level in newborns exposed to crack/cocaine during pregnancy and showed that BDNF level was higher in the umbilical cord and lower in the maternal blood compared to the control group. They suggested that the increase in BDNF levels in newborns exposed to crack/cocaine might indicate changes in fetal development, while the changes in BDNF levels in mothers provide evidence of the complex metabolic processes involved in drug use during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Ainda sob a perspectiva dos prejuízos fetais causados pelo uso de substâncias de abuso, dispõem-se que o estresse oxidativo (desequilíbrio entre a geração de compostos oxidantes) é fator responsável por patologias como: artrite, choque hemorrágico, doenças do coração, catarata, disfunções cognitivas, neoplasias e AIDS. O estresse oxidativo foi estudado por Mardini et al (2017), que, devido a meia vida curta das espécies reativas de oxigênio, quantificou um dos vários produtos dos danos produzidos pelo estresse oxidativo no corpo, o TBARS. Em recém-nascidos expostos às drogas ilícitas observa-se diminuição nos níveis de TBARS (marco da peroxidação lipídica) no sangue do cordão umbilical, fato que gera falha na homeostasia corporal e pode levar as patologias supracitadas.…”
Section: )unclassified